Radiographically Occult and Subtle Fractures: A Pictorial Review - Mohamed Jarraya; Daichi Hayashi; Frank W. Roemer; Michel D. Crema; Luis Diaz; Jane Conlin; Monica D. Marra; Nabil Jomaah; Ali Guermazi (Radiology Research and Practice)
Radiographically occult and subtle fractures are a diagnostic challenge. They may be divided into (1) “high energy trauma fracture,” (2) “fatigue fracture” from cyclical and sustained mechanical stress, and (3) “insufficiency fracture” occurring in weakened bone (e.g., in osteoporosis and postradiotherapy). Independently of the cause, the initial radiographic examination can be negative either because the findings seem normal or are too subtle. Early detection of these fractures is crucial to explain the patient’s symptoms and prevent further complications. Advanced imaging tools such as computed tomography, magnetic resonance imaging, and scintigraphy are highly valuable in this context. Our aim is to raise the awareness of radiologists and clinicians in these cases by presenting illustrative cases and a discussion of the relevant literature.